대기 중 마이크로플라스틱과 스타이렌 올리고머의 모니터링 - 권범근(Bum Gun Kwon) (Daehan hwan'gyeong gonghag hoeji, 2022)
목적 : 플라스틱으로 인한 환경오염은 중요한 환경적 이슈이다. 이 연구의 목적은 대기 중에 존재하는 마이크로플라스틱과 폴리스타이렌 (polystyrene, PS) 플라스틱에서 유래될 수 있는 인위적 화학종인 스타이렌 올리고머 (styrene oligomers, SOs) 12종을 모니터링하는 것이다. 방법 : 상기 목적을 달성하기 위해 이 연구는 광주광역시와 제주도 일원의 대기 시료를 채취하여 Fourier transformed infrared spectroscopy (FTIR)와 gas chromatography/mass spectroscopy (GC/MS)로 마이크로플라스틱과 12종 SOs 화학종의 농도를 정량적으로 분석하였다. 이 연구에서 마이크로플라스틱과 SOs 화학종의 시료 채취를 위해 스테인레스 스틸 필터를 사용하였다. 결과 및 토의 : 2019년 광주광역시 대기 중 조사된 SOs의 평균 농도는 0.24 (± 0.56) µg/m3이고, 2020년에 광주광역시 SOs의 평균 농도는 0.10 (± 0.16) µg/m3이었다. 또한, 2020년 제주도 SOs의 평균 농도는 0.11 (± 0.07) µg/m3인 것으로 모니터링되었다. 게다가, 2020년 광주광역시와 제주도 대기 중에 존재하는 마이크로플라스틱 농도는 0.13 개/m3에서 1.13 개/m3로 측정되었다. 이때, 검출된 마이크로플라스틱은 모두 9종이었고, 검출빈도가 가장 많은 마이크로플라스틱은 polyethylene (PE), polypropylene (PP), ethylene vinyl acetate (EVA), acrylate 재질이었다. 모니터링된 마이크로플라스틱의 모양(shape)은 모두 실 (fiber)과 조각 (fragment) 형태로, 아마도 대기 중 마이크로플라스틱이 주로 섬유에서 이탈되었거나 혹은 마찰과 파손에 의해 발생된 것으로 생각된다. 결과적으로, SOs와 마이크로플라스틱이 대기의 질을 평가하는데 새로운 오염 지표가 될 수 있다. 결론 : 이 연구는 SOs 화합물과 마이크로플라스틱에 관한 모니터링은 처음 시도하는 것이어서 플라스틱으로 인한 오염도 평가에 기여할 것으로 기대된다. Objectives : Plastic pollution is a very important environmental issue. The objective of this study is to monitor microplastics and styrene oligomers (SOs) as artificial chemical species that can be derived from polystyrene (PS) plastics. Methods : In order to achieve the above objective, this study collected atmospheric samples from the air of Gwangju City and Jeju Island and analyzed the concentrations of microplastics and SOs chemical species using Fourier transformed infrared spectroscopy (FTIR) and gas chromatography/mass spectroscopy (GC/MS). In this study, a stainless steel filter was used for the sampling of microplastics and SOs species. Results and Discussion : In 2019, the average concentration of SOs in the atmosphere of Gwangju City was 0.24 (± 0.56) µg/m3, and in 2020, the average concentration of SOs in Gwangju City was 0.10 (± 0.16) µg/m3. Those average concentration in Jeju Island in 2020 was monitored to be 0.11 (± 0.07) µg/m3. Moreover, the concentration of microplastics present in the atmosphere of Gwangju City and Jeju Island in 2020 ranged from 0.13 particles/m3 to 1.13 particles/m3. In this time, 9 types of microplastics were detected, and the most frequently detected microplastics were polyethylene (PE), polypropylene (PP), ethylene vinyl acetate (EVA), and acrylate materials. The monitored microplastic shapes were both fibers and fragments, suggesting that atmospheric microplastics are mainly released from fibers or caused by friction and breakage. Consequently, SOs and microplastics can be new pollution indicators for evaluating air quality. Conclusions : This study is the first attempt to monitor SOs compounds and microplastics, so it is expected to contribute to the evaluation of the extent of plastic pollution. KCI Citation Count: 0